Toxicological effects of cadmium on deep-sea mussel Gigantidas platifrons revealed by a combined proteomic and metabolomic approach - Zhou, Li; Li, Mengna; Zhong, Zhaoshan; Chen, Hao; Wang, Minxiao; Lian, Chao; Wang, Hao; Zhang, Huan; Cao, Lei; Li, Chaolun (Frontiers in Marine Science, 2023)
Introduction Marine metal contamination caused by deep-sea mining activities has elicited great concern from both social and scientific communities. Among the various metals deep-sea organisms might encounter, cadmium (Cd) is a widely detected metal that in very small amounts is nonetheless capable of severe toxicity. Yet due to both remoteness and technical challenges, insights into the effects of metal exposure resulting from mining activities upon deep-sea organisms are limited. Methods Here, we investigated Cd’s toxicological effects on deep-sea mussels of Gigantidas platifrons exposed to 100 or 1000 g/L of Cd for 7 days; an integrated approach was used that incorporated proteomics and metabolomics along with traditional approaches (metal concentrations, metal subcellular distribution, and anti-oxidative and immune-related biochemical indexes). Results and Discussion Results showed that Cd exposure caused significant Cd’s accumulation in mussel gills and redistribution of Cd among subcellular compartments, with cellular debris being the primary binding site. Although anti-oxidative enzymes activities (superoxide dismutase and catalase) were not significantly altered in mussel gills of both exposed groups, the markedly increased level of glutathione S-transferase detected via proteomic technique clearly evinced that deep-sea mussels suffered from oxidative stress under Cd exposure. Besides, altered activities of acid phosphatase and alkaline phosphatase assayed by traditional methods along with the predominant presence of largely altered immune-related proteins detected by proteomic data strongly revealed an immune response of deep-sea mussels elicited by Cd. In addition, results of proteomics combined with those of non-targeted metabolomics demonstrated that Cd could exert toxicity by disrupting cytoskeleton structure, ion homeostasis, and primary metabolisms of energy, lipid, and nucleotide in deep-sea mussels. As demonstrated in this study, proteomics and metabolomics can be used in tandem to provide valuable insights into the molecular mechanisms of deep-sea organisms’ response to Cd exposure and for helping to discover potential biomarkers for application during deep-sea mining assessments.